EXPLORATION OF FACTORS INFLUENCING SPIRITUAL INTELLIGENCE AMONG THERAVADA BUDDHISTS IN BANGKOK - Charoenchanaporn, Pakee; Madathil, Jayamala (Scholar: Human Sciences, 2015)
The topic of spiritual intelligence has received more interest from researchers as a new theory of intelligence in recent years. The current study attempted to investigate factors influencing spiritual intelligence. The factors were classified into three categories: three demographic factors (gender, age, socioeconomic status), two theoretically-related psychological constructs (universal-diverse orientation and cognitive flexibility), and seven religious practices (spreading Dhamma of Buddha, listening and discussing Dhamma with monks or Buddhist teachers, attending meditation courses, praying, giving food to monks, maintaining the Five Precepts, and meditating). Participants consisted of 200 Theravada Buddhists in Bangkok. Each participant was administered instruments which aimed to elicit self-reported ratings of spiritual intelligence (SI), universal-diverse orientation (UDO), and cognitive flexibility (CF). Regression analysis employing the forward selection procedure for entry of the predictive variables in predicting SI was conducted. Results revealed four factors that significantly predicted SI (in rank order), namely: (1) socioeconomic status, (2) religious practice of spreading Dhamma of Buddha, (3) age, and (4) universal-diverse orientation. The combination of these four factors explained significant variance in SI. Other factors examined were not significant in predicting SI. Based on the results, the researcher suggested that the practice of spreading Dhamma of Buddha (for Theravada Buddhists) and the practice of accepting differences in others (based on the UDO concept) should be fostered to increase SI. Further related studies along the same avenue are needed to identify other factors or practices that could influence SI among Theravada Buddhists.